2019
DOI: 10.3168/jds.2017-14083
|View full text |Cite
|
Sign up to set email alerts
|

Bulk tank raw milk microbiota differs within and between farms: A moving goalpost challenging quality control

Abstract: Microbial contamination of bovine raw milk often occurs at the farm. To acquire a deeper knowledge of the microbiota of farm tank milk, we studied milk from 45 farms situated in 2 geographical areas in Norway. Each farm was visited on 3 different occasions, with at least 2 wk between visits. We combined both bacterial cell counts and a sequence variant inference method of amplicon-based high-throughput sequencing to achieve a high-resolution overview of the microbiota in each sample. Compositional variation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
55
1
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 46 publications
8
55
1
8
Order By: Relevance
“…The complete removal of contaminations from the teat apex or the environment cannot be ensured by the results obtained in this study, and additional experiments are needed to compare microbiota from milk samples obtained pre- and post-milking. However, although some taxa associated with the environment, such as Bacillaceae and Pseudomonadaceae, were detected in the dataset their abundance was much lower (< 1%) than that found in milk collected from bulk farm tanks which included organisms present in cows as well as milk equipment and the farm environment 17 19 . Interestingly, by using this sampling regime, we obtained a microbiota that was highly dominated by two families ( Corynebacteriaceae and Staphylococcaceae ).…”
Section: Discussionmentioning
confidence: 74%
“…The complete removal of contaminations from the teat apex or the environment cannot be ensured by the results obtained in this study, and additional experiments are needed to compare microbiota from milk samples obtained pre- and post-milking. However, although some taxa associated with the environment, such as Bacillaceae and Pseudomonadaceae, were detected in the dataset their abundance was much lower (< 1%) than that found in milk collected from bulk farm tanks which included organisms present in cows as well as milk equipment and the farm environment 17 19 . Interestingly, by using this sampling regime, we obtained a microbiota that was highly dominated by two families ( Corynebacteriaceae and Staphylococcaceae ).…”
Section: Discussionmentioning
confidence: 74%
“…It was demonstrated that dairy farm environment influences milk microbiota (Vacheyrou et al, 2011;Skeie et al, 2019). For example, thermoduric sporeforming bacteria in milk can come from soil, silage, or bedding.…”
Section: Introductionmentioning
confidence: 99%
“…Although Turicibacter was enriched in slit containing cheese produced in 2015, members of this genus were not isolated under the growth conditions used here, potentially because strict anaerobic conditions were not applied [68]. Although members of this genus have yet to be isolated from milk and only three isolates from human and mice intestinal contents are known [68], Turicibacter appear to be pervasive in milk and have been detected in proportions over 1% in numerous studies investigating the microbiota of bovine milk and dairy products [4,[69][70][71][72]. Lastly, although most of the general quality characteristics of the commercial cheeses were indistinguishable, there was a modest but significant reduction in the salt content of cheeses that developed slits.…”
Section: Discussionmentioning
confidence: 94%